Winery wastewater treatment monitored using planted wetland common reed bed - ADOUNKPE, GNONLONFOUN JULIEN (My University, 2012)
Agro businesses use a great amount of water in the production processes. Consequently they are very concerned with wastewater treatment before any discharge. Wastewater from agribusinesses contains elevated concentration of organic matters and nitrogen. Winery wastewater gets high salinity, and depending on the daily, monthly or yearly production, it is characterized by a very variable flow. Physico-chemical ways of wastewater treatment use chemicals that can turn out be to pollutants or which can generate hazardous byproducts whereas biological treatment is more environmentally friendly by fitting into the landscape and not producing any potentially dangerous products. The constructed wetland with reed beds is the only biological treatment which can be both ecologically and costly efficient. Therefore an experimental constructed wetland with vertical flow reed beds was built to treat wastewater from BARDET’s vinery in France. The experience was run for 7 weeks. For average input concentrations of: TSS (335,4 mg/L), TKN (26,3 mg/L) and TP (6 mg/L)the output concentrations were the following: TSS (43,2 mg/L), TKN (11,1 mg/L) and TP (2,1 mg/L) . The average removal rates were: TSS (86,5%), TKN (61,8%) and TP (62,9%). The treated water had concentrations that were in line with the regulation set forth in the 02/02/98 decree which set the output concentration in a river at: TSS (100 mg/L), GN (30 mg/L) and TP (10 mg/L).
Keywords: onstructed wetlands; reed; winery wastewater